(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article examines effective methods for mastering Fergana-Tashkent maqom styles in the process of music education. The research reveals the importance of an integrated approach combining traditional and modern teaching methods, comprehensive study of theoretical and practical aspects of maqom art, use of modern technologies, and individual approaches. The article provides practical recommendations for teachers and students